Maternal hepatitis B e antigen can be an indicator for antiviral prophylaxis of perinatal transmission of hepatitis B virus. Issue 1 (1st January 2021) - Lu, Ying; Song, Yarong; Zhai, Xiangjun; Zhu, Fengcai; Liu, Jianxun; Chang, Zhanjun; Li, Yi; Xiao, Yiwei; Li, Lili; Liu, Minmin; Liu, Jia; Duan, Zhongping; et al.
ABSTRACT: As a high-risk factor of perinatal HBV transmission, the potential role of maternal hepatitis B e antigen (HBeAg) to guide antiviral prophylaxis has not yet been fully reported. This large prospective cohort study enrolled 1177 hepatitis B surface antigen (HBsAg)-positive pregnant women without antiviral treatment and their newborns. HBeAg, HBsAg, and viral load in maternal serum collected before delivery were measured. All the newborns were given standard passive–active immunoprophylaxis within 12 h after birth, and post-vaccination serologic testing was performed at 7 (±7d) months of age. The results revealed that 20 of the 1177 infants (1.70%) were immunoprophylaxis failure, and all their mothers were HBeAg positive. Maternal quantitative HBeAg was positively correlated with viral load ( r = 0.83; P < .0001) and quantitative HBsAg ( r = 0.68; P < .0001). The area under the receiver operating characteristic curve (AUC) for predicting immunoprophylaxis failure by maternal HBeAg was comparable to that by maternal viral load (0.871 vs 0.893; P = .441) and HBsAg (0.871 vs 0.871; P = .965). The optimal cutoff value of maternal quantitative HBeAg to predict perinatal infection was 2.21 log10 PEI U/mL, and the sensitivity and specificity was 100.0% and 74.5%, respectively. According to maternal viral load >2 × 10 5 IU/mL, the sensitivity and specificity of maternal qualitative HBeAg to identify the risk of HBV MTCT for pregnant women and determine the necessity for antiviral prophylaxis was 95.5% and 92.6%, respectively. This study showed that maternal HBeAg can be a surrogate marker of HBV DNA for monitoring and evaluating whether antiviral prophylaxis is necessary for preventing perinatal HBV transmission.